Lower Circulating Leptin Levels Are Related to Non-Alcoholic Fatty Liver Disease in Children With Obesity - Brandt, Stephanie; von Schnurbein, Julia; Denzer, Christian; Kratzer, Wolfgang; Wabitsch, Martin (Frontiers in Endocrinology, 2022)
Background: While for individuals with obesity an association between hyperleptinemia and an increased risk of non-alcoholic fatty liver disease (NAFLD) is assumed, a leptin deficiency is also related to the development of NAFLD early in life in ob/ob mice, in patients with leptin deficiency due to biallelic likely pathogenic variants in the leptin gene, and in patients with lipodystrophy. Objectives: To investigate the association of circulating leptin levels in pre-pubertal children with obesity and steatosis hepatis. Methods: The cross-sectional study consisted data of n=97 (n male=76) pre-pubertal children (11.8±1.5 years) with obesity (BMIz: 2.4±0.4). Fasting concentrations of cardiometabolic parameters were measured: insulin, c-peptide, glucose, triglyceride, cholesterol, HDL, LDL, AST, ALT, GGT, leptin. Steatosis hepatis was diagnosed by an ultrasound examination (mild, moderate or severe). Patients were categorized into two groups: low z-score of circulating leptin levels (≤25th percentile) vs. normal z-score of circulating leptin levels. Results: One-third of the children with obesity were diagnosed with steatosis hepatis (I°: 63.6%, II°/III°: 36.4%). Children with steatosis hepatis had significantly lower z-scores of circulating leptin levels compared to children with an unremarkable liver ultrasonography (-2.1±0.8 vs. -0.7±0.6). Z-scores of circulating leptin levels correlate negatively with degree of steatosis hepatis. Children with low z-scores of circulating leptin levels had significantly higher triglyceride, fasting insulin and c-peptide levels compared to children with normal z-scores of circulating leptin levels. Conclusion: Prepubertal children with NAFLD and obesity and partial leptin deficiency might be defined as a clinical subgroup.